A method of ATFCM based on trajectory based operations. - Gatsinzi, Dany (Cranfield University, 2018)
This thesis describes a method towards a more proactive approach for Air Traffic Flow and Capacity Management (ATFCM) Demand and Capacity Balancing (DCB). This new ATFCM DCB method focuses on reducing the expected Air Traffic Control (ATC) Separation Management (SM) tactical interventions. It is based on the identification of “hotspots” and mitigating them at pre-flight phase by applying minor adjustments on aircraft’s Times of Arrivals (TOAs) at points of conflict located at en-route crossing and merging junctions (hotspots). The adjustments of TOAs are achieved through optimal speed changes in aircraft speed profiles, applied before and after each junction whilst maintaining each aircraft’s flight time and the entropy of the whole traffic network. The approach postulates that the TOA adjustments may be transformed into a pre-tactical ATFCM DCB measure. This can be achieved by translating TOA adjustments into time constraints at junctions, issued by the Network Manager (NM) in the Reference Business Trajectories (RBTs) to produce de-randomized and well-behaved (conflict free) traffic scenarios to reduce the probability of conflicts. Several real high-density scenarios of the current and forecasted traffic in European Civil Aviation Conference (ECAC) airspace network are simulated using specialized modelling tools to validate the method. A novel Linear Programming (LP) optimisation model is formulated and used to compute optimal speed changes that remove all conflicts in the scenarios with minimum cascading effect. This method should enable a reduction in ATC workload, leading to improvements in airspace capacity, flight and network efficiency as well as safety. This approach is fully aligned to Trajectory Based Operation (TBO) principles. As a holistic solution, this new ATFCM DCB method should change the conventional capacity-limiting factor, currently established by the number of aircraft simultaneously entering each sector (sector count) to another factor where the level of traffic complexity, flying towards junctions is identified and mitigated at pre-flight phase.
Keywords: ATFCM; TBO; CD & R; DCB; junction; TOA; hotspot; complexity